plese answer 50 points
Attachments:
![](https://hi-static.z-dn.net/files/d51/a4b5cae20f8461c88b6ba0b18e236efd.jpg)
Answers
Answered by
2
нєяє ιѕ уσυя αиѕωєя мαтє...
Answer. Consider, 9x2-9(a+b)x+(2a2+5ab+2b2)=0 9x2 - 9(a + b)x + (2a2 + 4ab + ab + 2b2) = 0 9x2 - 9(a + b)x + [2a(a + 2b) + b(a + 2b)] = 0 9x2 - 9(a + b)x + [(a + 2b)(2a + b)] = 0 9x2 – 3[(a + 2b) + (2a + b)]x + [(a + 2b)(2a + b)] = 0 9x2 – 3(a + 2b)x - 3(2a + b)x + [(a + 2b)(2a + b)] = 03x[3x – (a + 2b)] - (2a + b)[3x + (a – 2b)] = 0 [3x – (a + 2b)][3x - (2a + b)] = 0 [3x – (a + 2b)] = 0 or [3x - (2a + b)] = 0 3x = (a + 2b) or 3x = (2a + b) x = (a + 2b)/3 or x = (2a + b)/3
Answer. Consider, 9x2-9(a+b)x+(2a2+5ab+2b2)=0 9x2 - 9(a + b)x + (2a2 + 4ab + ab + 2b2) = 0 9x2 - 9(a + b)x + [2a(a + 2b) + b(a + 2b)] = 0 9x2 - 9(a + b)x + [(a + 2b)(2a + b)] = 0 9x2 – 3[(a + 2b) + (2a + b)]x + [(a + 2b)(2a + b)] = 0 9x2 – 3(a + 2b)x - 3(2a + b)x + [(a + 2b)(2a + b)] = 03x[3x – (a + 2b)] - (2a + b)[3x + (a – 2b)] = 0 [3x – (a + 2b)][3x - (2a + b)] = 0 [3x – (a + 2b)] = 0 or [3x - (2a + b)] = 0 3x = (a + 2b) or 3x = (2a + b) x = (a + 2b)/3 or x = (2a + b)/3
Answered by
0
replace an instead of 5ab
Attachments:
![](https://hi-static.z-dn.net/files/d36/b8a31bd6d27346dffb9550efb454de47.jpg)
![](https://hi-static.z-dn.net/files/da2/c3eaf7b64a29a2304a1a478bd7adadd1.jpg)
Similar questions